The Effect of Origami Paper Folding Activities on the Fine Motor Skills of Group A Children at TK Negeri 5 Banda Aceh City - Julia Safitri; Riza Oktariana; Fitriani Fitriani (JUPE : Jurnal Pendidikan Mandala, 2026)
are typically sectioned logically as an overview of what appears in the paperThis study aimed to examine the effect of origami paper-folding activities on the fine motor skills of Group A children at TK Negeri 5 Banda Aceh. Fine motor skills are an important aspect of early childhood development involving the coordination of small muscles, particularly those of the hands and fingers, which are required for various daily learning activities such as writing, cutting, and drawing. This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The research sample consisted of 16 children selected through a total sampling technique. Data were collected through observation, performance tests, and documentation, and were analyzed using descriptive statistics and a paired sample t-test. The results showed a significant improvement in children's fine motor skills after the implementation of origami paper-folding activities. The mean pretest score was 7.56 (37.81%), while the mean posttest score increased to 15.31 (76.56%). The paired sample t-test revealed a significant difference with a significance value of 0.000 (p < 0.05), leading to the rejection of the null hypothesis. These findings indicate that origami paper-folding activities have a significant positive effect on improving the fine motor skills of early childhood children.